2016
DOI: 10.1021/acs.jpclett.5b02828
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Methylammonium Lead Iodide Perovskite Structures through Light and Electron Beam Driven Ion Migration

Abstract: Organometal halide perovskites show promising features for cost-effective application in photovoltaics. The material instability remains a major obstacle to broad application because of the poorly understood degradation pathways. Here, we apply simultaneous luminescence and electron microscopy on perovskites for the first time, allowing us to monitor in situ morphology evolution and optical properties upon perovskite degradation. Interestingly, morphology, photoluminescence (PL), and cathodoluminescence of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
232
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(255 citation statements)
references
References 29 publications
8
232
0
1
Order By: Relevance
“…It is also known that the crystallization of PNCs is another key parameter in relation to stability . Yuan's group reported that smaller clusters of cuboid MAPbI 3 NCs are more stable than the larger ones . This might be correlated to better crystallinity of the smaller clusters.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…It is also known that the crystallization of PNCs is another key parameter in relation to stability . Yuan's group reported that smaller clusters of cuboid MAPbI 3 NCs are more stable than the larger ones . This might be correlated to better crystallinity of the smaller clusters.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…Despite the high device efficiency, solution process at a low cost, and potential for large‐scale manufacturing, the stability of the perovskite solar cells is one major challenge that impedes commercialization . Several factors that affect the stability of hybrid perovskites have been systematically investigated, such as humidity, oxygen, heat, and irradiation . When exposed to humidity, the perovskite hydrate CH 3 NH 3 PbI 3 · x H 2 O forms, driving the perovskite crystal decomposition to PbI 2 .…”
Section: Introductionmentioning
confidence: 99%
“…While device efficiencies continue to soar, the stability of PSCs remains as a serious barrier to commercialization. To date, studies have shown that moisture, oxygen, elevated temperature, structural transformations, ultra‐violet light exposure, and sealing techniques all cause degradation of the perovskite photoactive layer and result in device instability . This in turn has led to the development of various strategies to improve film and device stability.…”
Section: Introductionmentioning
confidence: 99%